(untitled) (Diametros, 2009)
Decisions relating to action or inaction with regard to therapy is usually associated with ethical conflicts, since it affects fundamental values such as respect for the autonomy of the patient and the value of human life. The implementation of patient autonomy is possible only as a result of dialogue with the physician or medical personnel and loved ones. This can be achieved only as an ability of a living human being, and hence it cannot be in protected in competition with the value of life, but always as including it. In order to be able to respect both fundamental values it is necessary to take into account the mortality of a human being. The proximity and inevitability of death and the futility of therapeutic efforts will therefore be an important criterion affecting the ethical evaluation of decisions. The proposal to appoint hospital ethics committees would be very welcome, provided that these bodies have an advisory role and facilitate communication between the physician and the patient. Their activities could also contribute to the awareness of ethical issues at end of life.